State-level high school completion rates: Concepts, measures, and trends. - Warren, John Robert (Education Policy Analysis Archives, 2005)
Since the mid 1970s the national rate at which incoming 9th graders have completed high school has fallen slowly but steadily; this is also true in 41 states. In 2002, about three in every four students who might have completed high school actually did so; in some states this figure is substantially lower. In this paper I review state-level measures of high school completion rates and describe and validate a new measure that reports these rates for 1975 through 2002. Existing measures based on the Current Population Survey are conceptually imperfect and statistically unreliable. Measures based on Common Core Data (CCD) dropout information are unavailable for many states and have different conceptual weaknesses. Existing measures based on CCD enrollment and completion data are systematically biased by migration, changes in cohort size, and/or grade retention. The new CCD-based measure described here is considerably less biased, performs differently in empirical analyses, and gives a different picture of the dropout situation across states and over time.